2007
DOI: 10.1182/blood-2006-12-060343
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory virus infection among hematopoietic cell transplant recipients: evidence for asymptomatic parainfluenza virus infection

Abstract: The incidence of respiratory virus infection after hematopoietic cell transplantation (HCT) has probably been underestimated with conventional testing methods in symptomatic patients. This prospective study assessed viral infection episodes by testing weekly respiratory samples collected from HCT recipients, with and without symptoms reported by questionnaire, for 100 days after HCT. Samples were tested by culture and direct fluorescent antibody testing for respiratory syncytial virus (RSV), parainfluenza viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
217
2
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(230 citation statements)
references
References 48 publications
7
217
2
4
Order By: Relevance
“…Englund et al 7 observed that 5 of 163 (3.0%) bronchoalveolar (BAL) lavage samples from HSCT recipients with lower respiratory tract disease were tested positive for hMPV. Peck et al 8 observed a 5.8% cumulative incidence of hMPV in a prospective surveillance study in which patients were followed during four winter/spring seasons.…”
Section: Introductionmentioning
confidence: 99%
“…Englund et al 7 observed that 5 of 163 (3.0%) bronchoalveolar (BAL) lavage samples from HSCT recipients with lower respiratory tract disease were tested positive for hMPV. Peck et al 8 observed a 5.8% cumulative incidence of hMPV in a prospective surveillance study in which patients were followed during four winter/spring seasons.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, subclinical respiratory viral infection has been documented and is considered transmissible [13][14][15]. A recent study by Campbell et al, looking at clinical outcomes in patients with pre-HSCT viral detection and post-transplant viral detection found no increased mortality with asymptomatic viral detection including those with asymptomatic pre-transplant viral detection but did find increased mortality with symptomatic viral detection including those with symptomatic pre-transplant viral detection [4].…”
Section: Discussionmentioning
confidence: 99%
“…11 Routine use of this highly sensitive diagnostic PCR assay, however, should be approached with caution as in most patients following SCT, the presence of hMPV RNA in nasopharyngeal samples may not represent active viral disease or serve as an indication for antiviral therapy. [1][2][3] hMPV can lead to serious disease in SCT recipients, and intravenous ribavirin appears to be promising therapy that requires further investigation. …”
mentioning
confidence: 99%
“…2 The occasional hMPV upper respiratory tract infection often resolves spontaneously and the usual brief illness seldom progresses to the lower respiratory tract. 3 However, in severely immunosuppressed transplant recipients, hMPV may rarely cause life-threatening pulmonary 4,5 and brain infection. 6 Ribavirin disrupts viral purine metabolism and inhibits viral RNA polymerase.…”
mentioning
confidence: 99%